Post a New Question

function

posted by .

if y1=x^(2)+3x-1 and y2= x-5
find:
a. y1+y2
b. y1-y2
c. y1*y2

  • function -

    a. Y1 + Y2 =( X^2 + 3X - 1) + (X - 5),
    X^2 + 3X - 1 + X - 5,
    X^2 +4X - 6.

    b. Y1 - Y2 = (X^2 + 3X - 1) -(X - 5),
    X^2 + 3X - 1 -X + 5,
    X^2 + 2X + 4,


    c. Y1 * Y2 = (X^2 + 2X + 4) (X - 5),
    X^3 + 3X^2 - X - 5X^2 - 15X + 5,
    X^3 - 2X^2 - 16X + 5

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question